2018
DOI: 10.2147/lctt.s137410
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review of fetal adenocarcinoma of the lung

Abstract: Fetal adenocarcinoma of the lung (FLAC) is a rare tumor. It accounts for ~0.1%–0.5% of all pulmonary neoplasms. Due to its rarity, much of the world literature regarding FLAC comes from case reports and case series. FLAC is an adenocarcinoma resembling developing fetal lung in its pseudoglandular stage (8–16 weeks of gestation). It is distinguishable from pulmonary blastoma (PB) because it lacks the mesenchymal component which is a hallmark finding in PB. Due to differences in histopathology and clinical cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…Aberrant β-catenin nuclear/cytoplasmic staining pattern has been considered as a hallmark of LG-FLAC. 1 , 7 Another valuable IHC marker is p53, which is expressed strongly in HG-FLAC, but is nearly absent in LG-FLAC. It had been shown that ~80% of HG-FLACs display IHC evidence of neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant β-catenin nuclear/cytoplasmic staining pattern has been considered as a hallmark of LG-FLAC. 1 , 7 Another valuable IHC marker is p53, which is expressed strongly in HG-FLAC, but is nearly absent in LG-FLAC. It had been shown that ~80% of HG-FLACs display IHC evidence of neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal adenocarcinoma of the lung (FLAC) is a rare malignant lung tumor, accounting for 0.1% to 0.5% of all pulmonary neoplasms. 1 It was reported as a subtype of pleuropulmonary blastoma lacking a sarcomatous component in 1982, 2 and the term “well differentiated fetal adenocarcinoma of the lung” was introduced afterwards. 3 As the name implies, FLAC morphologically resembles a developing fetal lung during the pseudoglandular phase: complex glandular components with tubules are lined by glycogen-rich, nonciliated cells.…”
mentioning
confidence: 99%
“…2 The two FLAC subtypes, L-FLAC and H-FLAC, differ in multiple aspects, including histopathology and clinical characteristics. 5 L-FLAC is commonly detected in female patients in the third-fourth decade of their lives. Typically, the initial diagnosis of L-FLAC occurs during the early stages (I-II).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their different clinicopathological features, biological behavior and clinical outcome, FLACs are classified into low‐grade fetal adenocarcinoma (L‐FLAC) and high‐grade fetal adenocarcinoma (H‐FLAC) 2,3 . It has been reported that the incidence of FLAC in all pulmonary neoplasms accounts for an estimated 0.1% –0.5% 4,5 . One study recently revealed that the prevalence of L‐FLAC and H‐FLAC was 0.32% and 0.54% in Chinese patients, respectively 6 …”
Section: Introductionmentioning
confidence: 99%
“…2 , 3 It has been reported that the incidence of FLAC in all pulmonary neoplasms accounts for an estimated 0.1% –0.5%. 4 , 5 One study recently revealed that the prevalence of L‐FLAC and H‐FLAC was 0.32% and 0.54% in Chinese patients, respectively. 6 …”
Section: Introductionmentioning
confidence: 99%